Parents' influence on the development of their children's ethnic intergroup attitudes: a longitudinal analysis from middle childhood to early adolescence. Issue 2 (3rd March 2016) - Jugert, Philipp; Eckstein, Katharina; Beelmann, Andreas; Noack, Peter
Abstract: This study investigated to what extent parents' intergroup attitudes influence the development of their children's ethnic intergroup attitudes (i.e., ingroup bias), and which socialization factors moderate this influence. We report on a four-year longitudinal study of 213 children ( M age = 7.94) and their parents conducted in Eastern Germany. Findings showed significant interindividual differences in children's developmental trajectories, which could, in part, be explained by child gender, socio-economic status and parental attitudes. The influence of parents' intergroup attitudes was moderated by parenting style and parental similarity in attitudes both of which, our findings suggest, can make the transmission of parental attitudes more likely.